ANALISIS SIKAP BERBAHASA DALAM MEMBENTUK KARAKTER KESANTUNAN KOMUNIKASI SISWA SEKOLAH DASAR - Istiqomah, Nur; Dedi Romli Tri Putra; Atikah Mumpuni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to examine the role of language attitudes in the formation of polite communication character in elementary school students. The study used a qualitative approach with a case study method conducted at Pamengger 02 Public Elementary School. The research subjects consisted of 31 fifth-grade students. Data collection was conducted through observation activities and interviews with class teachers. The data obtained were then analyzed descriptively through the stages of data reduction, data presentation, and conclusion drawing. Data validity was strengthened by source triangulation techniques. The results of the study show that students' language attitudes are related to communication behavior that occurs in interactions in the school environment. Students' views on the use of Javanese also influence the way they communicate, both with teachers and with peers. Positive language attitudes can support the formation of polite communication character in students through the habit of using polite language in daily activities at school.